Emotional picture of catastrophy in Chernobyl (based on „Chernobyl prayer“ by Svetlana Alexievich) - Słupianek-Tajnert, Daria (Papers in Linguistics, 2019)
Chernobyl Prayer by Svetlana Alexievich is both a highly emotive and emotion-generating text. The Chernobyl disaster depicted in this work is permeated with emotionality. The dominant emotion is fear connected with an ever present motif of death, which affects human beings, the world of nature as well as all products of the human hand. Positive emotions are evoked in the context of the Chernobyl disaster serving the role of a uniting factor for the Belarusian people, or when the disaster is treated as a source of “new and powerful impressions”.